CONSUMER LOYALTY TOWARDS ENDORSEMENT ADVERTISING AND SERVICE QUALITY - Arifin Djakasaputra; Juliana Juliana; Florensia Irena; George Nicholas; James Austin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Business Development In Indonesia Is Also Increasing Rapidly And Experiencing Excellent Growth, One Of Which Is In The Business Sphere Or Food And Beverages (F&B) Industry And Dominated By Ownership Of Famous People One Example Is The Street Boba Brand That Has Beverage And Food Products. However, To Establish Loyalty To Consumers And Interest In Prospective Consumers Must Also Be Considered By The Street Boba Brand, Considering The Targets Are Also Different. Thus, In This Case, The Company Must Implement The Right Way To Form Consumer Loyalty That Will Increase Public Interest In Buying Street Boba Products And Support The Brand To Be Larger, One Of The Ways That Are Done By The Presence Of Endorsement Ads And Also Improvements To The Quality Of Services Provided To Those Consumers. So, In Further Research, Researchers Will Also Collect A Variety Of Data From Questionnaires To Data Obtained From The Internet, Involving Direct Correspondents Who Have A Target Age Of 17 Years To 25 Years And Love To Use Social Media And Is One Of The Consumers Of The Street Boba Brand. Furthermore, The Data Will Be Tested For Validity And Reliability Using Spss Application Assistance And Will Be Analyzed With A Quantitative Approach, And Will Generate Data That Signification Of Endorsement Advertising And Improvement Of The Quality Of Services Is Very Influential To The Form Of Consumer Interest And Consumer Loyalty Given To Street Boba.